ChemInform Abstract: Catalytic Activity of Layered Double Hydroxides or Hydrotalcite‐Type Anionic Clays. Issue 12 (14th March 2013) - Vaccari, Angelo; Basile, Francesco; Fornasari, Giuseppe
Abstract Review: 182 refs.